Writing as a Vocabulary Learning Tool - Bush, Jerome; Dikilitas, Kenan (Brill, 2014)
This study examined the impact of writing on the vocabulary acquisition of 32 universitypreparatory students in Izmir, Turkey. The students were in two separate classes of 16 each. Bothclasses learned vocabulary receptively by using direct explanations, readings that incorporatedthe target words, and post-reading exercises. In addition to this receptive work, one classproduced sentences and short compositions incorporating the target words. The students wereevaluated by using a modified version of Paribakht and Weshe’s (1997) Vocabulary KnowledgeScale and t-tests were performed. It was found that writing had a significant effect on thedevelopment of productive vocabulary.
Keywords: writing, vocabulary, VKS, voicabulary acquisition, academic writing